Assessment of socio-ecological efficiency of motor transport company with transaction expenses - Zagurskіy, Oleg (Management and Entrepreneurship: Trends of Development, 2019)
There are a lot of research of scientists and practitioners about the significant impact of the transport factor on economic development and the emergence of market institutions. However, it’s important to pay attention to the question of the transport and institutional factors interaction and their impact on the efficiency of the country economic development.Purpose. The purpose of the research is to analyze the theoretical and methodological aspects of the transport and institutional factors influence on the country economic development and to solve the methodological problem of determining and estimating transaction costs in the economic analysis of the socio-ecological efficiency of the operation of motor transport companies.Design/methodology/approach. System-evolution and system-structural approaches have been used in the article. They are necessary for a coherent research to identify the various characteristics and dependencies which come up in the process of determining the assessment methodology of the socio-ecological efficiency of motor transport companies with transaction costs.Findings. New approaches of the synergistic effect analysis of the transport and institutional factors interaction which contributes to the structural replacement of other industries transport costs leading to overall economic growth have been formed in the research. So, it is expedient to introduce appropriate methods for institutional interactions assessment in a market economy into the methodology of economic assessment of socio-ecological efficiency of motor transport companies.Research limitations/implications. The coefficient of socio-ecological efficiency shows the size of the motor transport company and society benefits from the lost financial resources for improving its socio-ecological efficiency and transaction costs for establishment of effective interactions with participants of institutional changes.Originality/value. The research has practical content. Theoretical and methodological thesis, conclusions and recommendations permit to accept scientifically substantiated effective administrative decisions on realization of the transport and technological schemes of the cargoes and passengers delivery; have quantitative criteria for assessment of the proposed socio-ecological efficiency measures; to evaluate the efficiency of the state regulation system of motor transport activity on the basis of developed approaches.